Effects of using different materials at interface of trapezoidal reinforced concrete infilled frames–analytical and experimental approaches - Vishali, Mugunth; Bahrami, Alireza; Satyanarayanan, Kachabeswara Srinivasan; Thirumurugan, Varatharajan; Prakash, Murugan (Frontiers in Materials, 2023)
Infilled frames are formed by the composite interaction of the bounding planar frame and infilling wall provided for functional purposes under in-plane lateral loading. The composite interaction increases the in-plane lateral stiffness of the frame, which is considered to be its advantage. However, the interaction also alters the ductile mode of failure to the brittle mode along with increased base shear due to its higher stiffness as compared with bare frame. The detailed and comprehensive study of the literature reveals that the majority of work is done on rectangular and square frames, and studies on trapezoidal infilled frames are very scarce. In this article, it is attempted to study the different configurations of reinforced concrete frame structures known as trapezoidal frames, which have more stiffness than the former. Trapezoidal frame is used for industrial buildings, and their behavior under lateral load is already established for the bare frame. However, the interaction and behavior of the infilled frame are investigated in this study. A study was conducted to investigate the behavior of a trapezoidal, single-story frame under both lateral loading and various interface materials. One of the most frequently suggested methods is equivalent diagonal strut by researchers for infilled frame analysis. Effective strut width design recommendations are available for rectangular and square frames but not for trapezoidal frames for macro modeling. Hence, to make the design easier, an effective diagonal width is developed for different interface materials with respect to the relative stiffness of various frame cross-sections, and further validation with a frame of ideology from biomimicry using nature of one-sixth scale model is tested. The effective strut width for the trapezoidal infilled frame varies between d/8 and d/9 for the cement mortar and cork interfaces, where ‘d’ is the diagonal length of the frame.